H[Na(H2O)3]6F(PO4)2 ⋅ 2(H2O): A New Polycation‐Type Phosphate with Deep Ultraviolet Transparency. Issue 45 (18th November 2021) - Yang, Xukui; Liu, Yuting; Li, Yuxin; Ma, Peixin; Zeng, Tixian; Duan, Meihong; Fang, Zhi; Qin, Dabin
Abstract: A new polycation‐type phosphate of H[Na(H2 O)3 ]6 F(PO4 )2 ⋅ 2(H2 O) (FNPO) was synthesized by a mild hydrothermal method. FNPO crystallizes in the cubic space group of F d 3 ‾ c with cell parameters of a =27.778 Å and Z=32. In the structure of FNPO, every sodium ion is six‐fold coordinated to five water molecules and one fluoride ion in forming electroneutral [NaF(H2 O)5 ] octahedra, while one kind of super octahedral polycation‐type [Na(H2 O)3 ]6 F 5+ complexes with center anion of F ‐ is constructed by six [NaF(H2 O)5 ] octahedra via the sharing of their terminal fluoride ion and water molecules. Besides counter cation of [Na(H2 O)3 ]6 F 5+ complexes, all the other (PO4 ) 3− and water molecules are in a discrete arrangement with sole connection of hydrogen‐bond interaction with [Na(H2 O)3 ]6 F 5+ complexes in forming [ 101 ]‐oriented pseudo‐lines, while each line is hydrogen‐bonded to six adjacent lines in generating the three‐dimensional structure of FNPO. Benefitted by this polycation‐type structure, FNPO was characterized by a deep ultraviolet transparency. Abstract : Polycation‐type structures are emerging functional structural motifs for the design of crystals with wide band gap. Herein, a new polycation‐type phosphate of H[Na(H2 O)3 ]6 F(PO4 )2 ⋅ 2(H2 O) was rationally developed. H[Na(H2 O)3 ]6 F(PO4 )2 ⋅ 2(H2 O) crystal is characterized by super octahedral polycations of [Na(H2 O)3 ]6 F 5+ and deep ultraviolet transparency, highlighting the promising future of finding applicable polycation‐type deep ultraviolet optical crystals.